ANALISIS RANTAI NILAI (VALUE CHAIN) USAHA AGROINDUSTRI PAKAN IKAN DI KECAMATAN KUOK KABUPATEN KAMPAR - Novia Dewi; Jum'atri Yusri; Leonardo Tobing (Indonesian Journal of Agricultural Economics, 2018)
The purpose of this research was to analyze the value chain, margins, and value-added of fish food agroindustries in district of Kuok Kampar Regency. The method of taking respondents was conducted by census where total population in Kuok district was 5 fish food producers. The results showed the mapping activities and actors involved in the value chain, the value of the margin and the value added of fish food products. Actors involved in the value chain of fish feed is the suppliers of raw materials, manufacturers of fish food, and retailers. There are 2 activities in the value chain of fish food, that are primary and secondary activities. The profit margin value received by producers in the value chain of pattern I is IDR 785/kg. The value of the profit margin of producers in the value chain pattern II is IDR 726,03/kg and the value of the received profit margin retailers in chain the value of pattern II is 1.858,58/kg. The value of marketing efficiency in the value chain of patterns I of 8.34% and the value of the marketing efficiency in pattern II is 7.92%.  The value chain of pattern II is more efficient because producers did not issue the transport costs in the sale of fish food. The value added of the raw material into fish food is IDR 3.648/kg fish food.